Integrating Ontology-Based Approaches with Deep LearningModels for Fine-Grained Sentiment Analysis - Zhao, Longgang; Lee, Seok Won (Computers, Materials and Continua, 2024)
Although sentiment analysis is pivotal to understanding user preferences, existing models face significant challenges in handling context-dependent sentiments, sarcasm, and nuanced emotions. This study addresses these challenges by integrating ontology-based methods with deep learning models, thereby enhancing sentiment analysis accuracy in complex domains such as film reviews and restaurant feedback. The framework comprises explicit topic recognition, followed by implicit topic identification to mitigate topic interference in subsequent sentiment analysis. In the context of sentiment analysis, we develop an expanded sentiment lexicon based on domainspecific corpora by leveraging techniques such as word-frequency analysis and word embedding. Furthermore, we introduce a sentiment recognition method based on both ontology-derived sentiment features and sentiment lexicons. We evaluate the performance of our system using a dataset of 10,500 restaurant reviews, focusing on sentiment classification accuracy. The incorporation of specialized lexicons and ontology structures enables the framework to discern subtle sentiment variations and context-specific expressions, thereby improving the overall sentiment-analysis performance. Experimental results demonstrate that the integration of ontology-based methods and deep learning models significantly improves sentiment analysis accuracy.
Keywords: Analysis accuracy; Deep learning; Fine grained; Fine-grained sentiment analyze; Learning models; Online reviews; Ontology's; Ontology-based methods; Sentiment analysis; Sentiment lexicons; Deep learning; fine-grained sentiment analysis; online reviews; ontology